PENERAPAN MODEL TSTS UNTUK MENINGKATKAN KEPERCAYAAN DIRI MAHASISWA PRODI PENDIDIKAN MATEMATIKA UNIVERSITAS MUHAMMADIYAH PONOROGO PADA MATA KULIAH TEORI BILANGAN - Uki Suhendar (Universitas Muhammadiyah Ponorogo, 2017)
Self confidence in learning must be owned by students. However, the fact that happened to the students of semester 1 year 2016/2017 in Fondasi Matematika course still not maximal. Teori Bilangan is a course given to students of the second semester of mathematics education program at Muhammadiyah University of Ponorogo. The purpose of this research is to increase students' self confidence in the subject of Teori Bilangan using Two Stay Two Stray learning model. Thus it is expected that students will be more confident in learning in other subjects in Mathematics Education program. This classroom action research is conducted in two cycles. Results of data analysis before the implementation of the study is 18.52% of the overall students who have high confidence. After analyzing the final data of cycle 2, it is found that the percentage of students who do not have high confidence is 22.22%. The TSTS steps used to improve students' self-confidence is with the improvement effort in the form of lecturers providing assistance to groups that have difficulty in solving the LKM problem..